RESEARCH AND CALCULATION OF THE ZONE OF CONFIDENT SIGNAL RECEPTION OF DIGITAL SOUND RADIO BROADCASTING TRANSMITTER'S SIGNAL (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
The article examines current trends in the development of digital radio broadcasting, including the transition from analog to digital signals, the development of standards and their application in various countries. Special attention is paid to the relevance of research and calculation of digital broadcasting coverage areas, which is crucial for optimizing infrastructure, uniform access to information and ensuring high-quality services. Examples of successful implementation of digital radio broadcasting technologies in developed countries, including Norway, Great Britain, Germany, and Switzerland, are given. A generalized algorithm for calculating the safe reception zone of a digital audio broadcasting transmitter is proposed.
Keywords: digital broadcasting; coverage area; DAB/DAB; DAB; HD Radio standards; radio wave propagation; terrain relief